Efficacy of detoxifying and palliative Ayurvedic treatment on survival and quality of life in triple negative breast cancer patients - Sadanand Prabhakar Sardeshmukh; Arvind Vishnu Kulkarni
Triple Negative Breast Cancer (TNBC) accounts for ~10-20% of invasive breast cancers and has an early recurrence and aggressive metastases. It is a heterogeneous disease based on immunohistochemistry as estrogen, progesterone, and human epidermal growth factor-2 receptors are negative. Thus, hormonal treatment is not offered to TNBC patients after completion of conventional treatment like other types of breast cancer patients. In this scenario, alternative medicines like Ayurveda are the day$1 (Bs need. According to Ayurveda, vitiated Vata, Pitta, and Kapha impair Jatharagni (digestive power) and Dhatvagni (digestive power of each tissue), disrupting dhatu metabolism (Rasa to Meda). This forms deep, firm, slow-growing, non-suppurative tumors at impaired sites like the breast, with progressive dhatu (deeper tissue) involvement (Dhatugatavastha), which is known as Dushta Stana Granthi (malignant breast nodes) or Arbuda (malignant breast tumour). In such a situation, Ayurveda describes Shamana (Dosha pacification), Rasayana (Rejuvenation), and Shodhana i.e., Panchakarma (body detoxification) as the main treatment modalities. Oral Ayurvedic medicines (OAM) consisting of Shamana and Rasayana are known to improve quality of life and immunity boosting in many diseases including cancer whereas Panchakarma (PNK) detoxifies body and thus helps to minimize the risk of recurrence. The main aim of this study was to study the efficacy of Ayurvedic treatment as well as comparing effect of treatment modalities viz., Shamana with Rasayana (SR) and Shamana with Rasayana and Panchakarma (SRP) on survival and Quality of life (QoL) in TNBC patients. In this retrospective study, 68 patients diagnosed with TNBC, irrespective of stage and grade, with ongoing or completed conventional treatment and taken Ayurvedic treatment for more than 6 months were included. QoL was studied by using standard questionnaires while Disease-free Survival (DFS) and Overall survival (OS) were assessed by radiological and biochemical parameters. DFS was found in maximum patients (75%) and progression in only 25% of patients also highlight the efficacy of Ayurvedic treatment to control the disease. Longer DFS and OS were seen in the patients treated with SRP as compared to SR. Significant improvement in functional, symptom, global, and Karnofsky performance scores of all patients indicated improved QoL and well-being after Ayurvedic treatment. These results are indicative of efficacy of Ayurvedic treatment to increase survival and improve QoL of TNBC patients. Especially, SRP treatments are more beneficial to increase DFS and OS thus emphasizing the necessity of detoxifying PNK treatment in addition to OAM in TNBC patients.s